Simulation of a low-voltage distribution network when arranging voltage stabilizers - Aluynov A.; Vyatkina O.; Gracheva E.; Bylanov S. (E3S Web of Conferences, 2021)
A computer algorithm for optimal voltage regulation using voltage stabilizers is presented. The applied voltage stabilizers are suitable for operation with radial distribution networks, taking into account various load models. The proposed algorithm makes the initial selection, installation, and adjustment of voltage stabilizers, which provide smooth voltage regulation throughout the network, using the existing algorithms, which are appropriately modified and optimized. The algorithm is fast, efficient, and reliable, which is confirmed by its practical application in distribution networks.